Cholangitis in patients with atrial fibrillation: A retrospective cohort study in Taiwan. Issue 6 (11th February 2022) - Hu, Wei-Syun; Lin, Cheng-Li
Abstract : Abstract: The purpose of this study is to investigate whether atrial fibrillation (AF) and cholangitis is associated. This is a propensity-matched retrospective cohort report from the Taiwan National Health Insurance Research Database. We included patients who had AF but didn't have cholangitis, and matched controls between January 1, 2000 and December 31, 2012. The AF cohort comprised 114, 572 patients and the comparison cohort comprised 114, 572 subjects. All participants were followed up until developing cholangitis, death, or December 31, 2013, whichever came first. The cox model was used to calculate the adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for comparing the risk of cholangitis in the AF cohort and non-AF cohort. The incidence of cholangitis was higher in patients with AF than in those without AF [4.2 and 2.54 per 1000 person–years; adjusted HR (95%CI), 1.92 (1.54, 2.41)]. Comparing to subjects without AF, patients with AF had higher risk of cholangitis in the subgroup of ≥65 years (adjusted HR = 1.76, 95%CI = 1.40–2.21), female (adjusted HR = 2.51, 95%CI = 1.74–3.63), male (adjusted HR = 1.60, 95%CI = 1.19–2.14), without comorbidities (adjusted HR = 1.79, 95%CI = 1.23–2.61), and with comorbidities (adjusted HR = 1.85, 95%CI = 1.73–1.99). AF is associated with a higher incidence of cholangitis. The need of further investigations is mandatory because of the inherent limitations of observational study.